Little Tokyo Service Center : "Welcome to Little Tokyo, Please Take Off Your Shoes" - Silver, Nora, (SAGE business cases., 2022)
Little Tokyo Service Center (LTSC), a nonprofit founded in Los Angeles in 1979, adopted the tagline "Welcome to Little Tokyo, Please Take Off Your Shoes" to honor a Japanese tradition and defend against gentrification and displacement where demographics shifted dramatically. From its roots as a multipurpose social service center for Japanese Americans to building affordable housing for all, LTSC continually pivoted. LTSC tried to balance its original mission with population changes due to WWII internment camps, growing homelessness in Skid Row, and multiple ethnicities moving into Little Tokyo. LTSC leaders said while history should be valued, culture evolved and newcomers were not enemies. In 2022, LTSC navigated a high-visibility housing project balancing longstanding community stakeholders with newer residents. Could leadership-staff and board-manage the reputational risks of developing FSN with its cultural space, legacy businesses, and permanent supportive housing in a manner that met all constituents' expectations?